A (des)articulação das organizações da sociedade civil em ações de geração de trabalho e renda: o caso do bairro Jaguaré, município de São Paulo - Ferreira, Camila Cristina (2011)
This thesis aims to understand how the relationship between civil society organizations, working in the area of job and income generation in the neighborhood of Jaguaré, Municipality of São Paulo, Brazil, aiming to understand its implications. The methodology used was case study. Ten semi-structured interviews were conducted with representatives of the organizations surveyed. From the interviews several themes could be analyzed: information about organizations, programs, projects and actions, challenges, partnerships, the role played by specific organizations, the relationship between civil society organizations working in Jaguaré; and the relationship between these organizations and the Government. The entities surveyed clearly portray the variety of existing civil society organizations, and have different missions, sizes, modes of operation and impacts. Despite the large number of civil society organizations present at the District of Jaguaré, one realizes that there is a lack of networking, partnerships and synergies.